Diagnosing acute lower respiratory tract infections in out-of-hours services during the COVID-19 pandemic - Bent Håkan Lindberg; Beatriz González López-Valcárcel; Jonas K. Olsen; Malene Plejdrup Hansen; Jesper Lykkegaard; Carl Llor; Lina Jaruseviciene; Bruno Pascale; Maria-Nefeli Karkana; Ana García-Sangenís; Anna Kowalczyk; Ingrid Rebnord (International Journal of Emergency Medicine)
Abstract Background Acute lower respiratory tract infections (LRTIs) commonly lead people to seek out-of-hours primary care. Symptoms of lower respiratory tract infections overlap, and access to definite diagnostic tools is lacking in most out-of-hours settings. Distinguishing between different LRTIs is vital to ensure appropriate antibiotic prescribing. The study aimed to identify which clinical factors have guided out-of-hours physicians in distinguishing LRTIs in the late phase of the COVID-19 pandemic. Methods Out-of-hours physicians from France, Greece, Lithuania, Poland, and Spain registered pre-defined clinical information about all cases suspected of an RTI on an A4-paper Audit Project Odense chart from January to March 2022. Two multivariable logistic regressions were performed to analyse which clinical factors the physicians used to distinguish between pneumonia and other LRTIs. Results A total of 1,222 cases of either pneumonia, acute bronchitis/bronchiolitis, common cold/influenza, or COVID-19 were registered by 86 participating physicians. Fever and cough were the most common symptoms reported. The pneumonia diagnosis was associated with abnormal lung auscultation (odds ratio (OR) 11.41, 95% confidence interval (CI) 4.14–31.45), poor general condition (OR 5.96, CI 2.43–14.60), tachypnoea (OR 2.55, CI 1.38–4.73), and a combination of fever and cough (OR 11.10, CI 2.87–42.97). Conclusion During the late COVID-19 pandemic, out-of-hours physicians’ registered information about the patients’ clinical condition, respiratory rate assessment, and lung auscultation evaluation were associated with diagnosing pneumonia, among other LRTIs.